Pengaruh Defatting, Frekuensi Pencucian dan Penyimpanan Beku Terhadap Kualitas Surimi Ikan Lele - Anhar Rozi; Ikhsanul Khairi; Reni Tri Cahyani; Stephani Bija; Nurhikma Nurhikma; Nuring Wulansari; Deden Yusman Maulid; Siluh Putu Sri Dia Utari; Diah Anggraini Wulandari (Universitas Sriwijaya, 2020)
Catfish was a suitable alternative for the main raw material for making surimi, because it has a high protein content, easy to found and than has good prospective to be made surimi product. The aimed of this study to analyze effect of defatting, washing cycle, and frozen storage was add cryoprotectant. This research was conducted three step that is deffating, washing, and made surimi. The concentration of the selected for defatting processed was NaH2PO4 2% during 10 minutes and the result fat content was 0.15%. The best washing was one time of made kamaboko and has gel strength (510.35 g.cm), and the best quality (PLG : 0%; pH : 6.53; water content : 76.6%; folding test : 3.22; bite test : 3,77) when compared with washing cycle two times and three times. The best cryoprotectant addition was 4% trehalose and result of gel strength was 354.15 g.cm for three weeks of frozen storage.